2000
DOI: 10.1073/pnas.040580197
|View full text |Cite
|
Sign up to set email alerts
|

The olfactory receptor gene repertoire in primates and mouse: Evidence for reduction of the functional fraction in primates

Abstract: olfaction ͉ pseudogenes ͉ evolution

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
177
1
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(190 citation statements)
references
References 31 publications
(38 reference statements)
5
177
1
2
Order By: Relevance
“…As a result, apes and Old World monkeys have many fewer OR pseudogenes than humans. Nonetheless, the proportion of OR pseudogenes in these nonhuman primates is still significantly higher than those of dog or mouse (Rouquier et al 2000;Gilad et al 2003b). Taken together, the data suggest that a deterioration of the olfactory repertoire occurred during primate evolution, with a particularly steep decline in the human lineage.…”
supporting
confidence: 52%
“…As a result, apes and Old World monkeys have many fewer OR pseudogenes than humans. Nonetheless, the proportion of OR pseudogenes in these nonhuman primates is still significantly higher than those of dog or mouse (Rouquier et al 2000;Gilad et al 2003b). Taken together, the data suggest that a deterioration of the olfactory repertoire occurred during primate evolution, with a particularly steep decline in the human lineage.…”
supporting
confidence: 52%
“…As a result, haplorhines have generally been characterized as lacking well-developed olfactory abilities. However, recent comparative studies of the MOS suggest that platyrrhines resemble strepsirrhines and many other mammals in retaining a large proportion of functional ORP genes (92)(93)(94). Because the olfactory bulb is primarily a relay between MOS receptors in the nasal fossa and olfactory centers in the brain, the small size of the platyrrhine olfactory bulb probably reflects a decrease in the total number of MOS receptor cells rather than a decrease in the number of distinct ORP types.…”
Section: Adaptations In Anthropoideamentioning
confidence: 99%
“…Furthermore, even the apes and the Old World monkey comparisons may have not been accurate, because the use of degenerate primers may have biased the results. Indeed, Rouquier et al (10) report zero pseudogenes in mouse and 70% pseudogenes in humans (where they looked at 99 ORs). These values are significantly different from the true values obtained once the entire OR gene repertoire was reported for these species (20% and 58%, respectively).…”
mentioning
confidence: 99%
“…Although three to five of these 14 OR loci were found to carry coding region disruptions in one or more ape species, all 14 OR genes were inferred to be intact in the common ancestor of all apes (9). A different study (10) used OR degenerate primers to examine the OR gene repertoire in different mammals. On the basis of a small number of genes in non-human primates (18)(19)(20)(21)(22)(23), Rouquier et al (10) concluded that humans and apes have significantly more pseudogenes than Old World monkeys.…”
mentioning
confidence: 99%